2001
DOI: 10.1029/2001jd900196
|View full text |Cite
|
Sign up to set email alerts
|

Validation of land surface models using satellite‐derived surface temperature

Abstract: Abstract. This research examines the feasibility of using remotely sensed surface temperature for validation and updating of land surface hydrologic models. Surface temperature simulated by the Variable Infiltration Capacity (VIC) hydrologic model is compared over the Arkansas-Red River basin with surface temperature retrievals from TOVS and GOES. The results show that modeled and satellite-derived surface temperatures agree well when aggregated in space or time. In particular, monthly mean temperatures agree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…VIC is a physically-based macroscale hydrological model developed to solve water and energy balances. It has been applied in many parts of the world in a range of climate conditions and resolutions (Abdulla and Lettenmaier, 1997;Lohmann et al, 1998b;Matheussen et al, 2000;Durre et al, 2000;Nijssen et al, 2001;Rhoads et al, 2001;Christensen et al, 2004;Haddeland et al, 2006;Adam et al, 2007). VIC has been demonstrated to perform especially well in simulating streamflow in humid environments (Abdulla and Lettenmaier, 1997).…”
Section: The Variable Infiltration Capacity (Vic) Modelmentioning
confidence: 99%
“…VIC is a physically-based macroscale hydrological model developed to solve water and energy balances. It has been applied in many parts of the world in a range of climate conditions and resolutions (Abdulla and Lettenmaier, 1997;Lohmann et al, 1998b;Matheussen et al, 2000;Durre et al, 2000;Nijssen et al, 2001;Rhoads et al, 2001;Christensen et al, 2004;Haddeland et al, 2006;Adam et al, 2007). VIC has been demonstrated to perform especially well in simulating streamflow in humid environments (Abdulla and Lettenmaier, 1997).…”
Section: The Variable Infiltration Capacity (Vic) Modelmentioning
confidence: 99%
“…However, the ability to calibrate a model using satellite data, even in combination with traditional in situ data, is still a challenging topic. Scientific work in this field goes in many directions: Rhoads et al (2001) used satellite-derived LST to validate a land-surface model, Caparrini et al (2004) and Sini et al (2008) assimilated remotely sensed measurements into a land-surface model to estimate the surface turbulent fluxes, Brocca et al (2011a) analyzed different remotely sensed soil humidity estimations with the perspective of using them in hydrological modeling, White and Lewis (2011) used satellite imagery to monitor the dynamics of wetlands of the Australian Great Artesian basin and Khan et al (2011) have recently proposed a procedure to calibrate a fully distributed hydrological model using satellite-derived flood maps.…”
Section: Introductionmentioning
confidence: 99%
“…Its close conceptual link to terms of the surface energy balance and widespread availability suggests that spaceborne surface radiometric temperature ( T s ) retrievals in particular have some calibrational value for evapotranspiration predictions. Recent work has examined the value of remote T s retrievals as a source of validation data for land surface models [ Jin et al , 1997; Rhoads et al , 2001] and demonstrated the utility of T s observations within the context of land surface data assimilation systems [ Lakshmi , 2000; Boni et al , 2001]. The goal of this paper is to clarify the potential for improving large‐scale (>50 2 ‐km 2 ) model predictions of evapotranspiration through calibration of a land surface model using remote surface radiometric temperature retrievals.…”
Section: Introductionmentioning
confidence: 99%